2020
DOI: 10.1177/0954405420921721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Al2O3 powder addition on the metal removal rate and the surface roughness of the electrochemical grinding machining

Abstract: The integrated electrochemical grinding machining has received wide acceptance in the aircraft turbine industry for the machining of blades, vanes, and honeycomb seal rings. Also, medical devices, instruments and forceps, shells, precision nozzles, instrument coupling, and air rotor motors that produced from stainless steel and new materials have all successfully been accomplished with electrochemical grinding. To improve the metal removal rate and to reduce the surface roughness ( Ra) of the electrochemical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Yehia et al reported in 2020 that the effect of the Al 2 O 3 abrasive content on the metal removal rate and the Ra of the K110 steel using electrochemical grinding at different voltages, feed rates, electrolyte NaCl concentrations, and various depths of the cut were investigated [11]. The results revealed that the abrasive, electrochemical grinding was better than the electrochemical grinding results.…”
Section: Introductionmentioning
confidence: 99%
“…Yehia et al reported in 2020 that the effect of the Al 2 O 3 abrasive content on the metal removal rate and the Ra of the K110 steel using electrochemical grinding at different voltages, feed rates, electrolyte NaCl concentrations, and various depths of the cut were investigated [11]. The results revealed that the abrasive, electrochemical grinding was better than the electrochemical grinding results.…”
Section: Introductionmentioning
confidence: 99%
“…high hardness, chemical stability, strength, corrosion resistant, low thermal expansion coefficient, cost, etc.). 8,9…”
Section: Introductionmentioning
confidence: 99%
“…3 Electrochemical machining (ECM) is a noncontact material removal technology in which electrochemical dissolution takes place on the workpiece surface governed by a specific cathode shape. 4 Among its advantages are an ability to machine materials regardless of their hardness, 5 an absence of cutting stress and of micro-deformation, and high machining efficiency. 6…”
Section: Introductionmentioning
confidence: 99%